Application of Bamboo Composite for Unmanned Aerial Vehicle Rod Structure - Muslim, Najwa; Md Arifin, Latifah; Rahim, Mohammad Zulafif (Progress in Aerospace and Aviation Technology, 2023)
Researchers are exploring the use of natural fibers, such as bamboo fibers, as a replacement for synthetic fibers in composite materials due to environmental concerns and rising costs. Bamboo fibers have several benefits, including low cost, biodegradability, light weight, and good mechanical qualities. This study focused on the mechanical and physical characteristics of bamboo fiber composites for drone structures. Tensile tests were conducted, revealing a relatively low tensile strength ranging from 22026.99 to 5474.92 N/m3 compared to carbon fibre composites. The tensile strength was influenced by the composition and ratio of bamboo fibre and epoxy. The density of the bamboo fibre composite ranged from 0.9720 to 0.7790 g/cm3, which is lower than carbon fibre composites. Increasing the bamboo fibre content resulted in a decrease in density.